The Effect of Work Motivation and Interpersonal Communication on Teacher Performance in Elementary Schools in Medang Kampai Dumai - Susanti, Mega (Journal of Educational Sciences, 2021)
Teacher performance is very important and is the spearhead of the world of education. If the teacher's performance is good, the quality of the school will also be good. This study aims to analyze the effect of work motivation and interpersonal communication either partially or simultaneously on the performance of teachers in elementary schools in Medang Kapai Dumai. This research was conducted in Dumai for elementary school teachers in Medang Kampai sub-district with a total sample of 95 people using a quantitative approach with a simple random sampling technique. Data was collected by means of a questionnaire by conducting a trial first to see the validity and reliability. Furthermore, the data were analyzed with multiple regression. The results showed that either partially or simultaneously, work motivation and personal communication had a positive and significant effect on teacher performance. And the contribution to the two variables is 51.4% and the rest is influenced by other factors not examined in this study. Because the high and low teacher performance is determined by work motivation and interpersonal communication factors, it is expected that teachers always work together with school principals and fellow teachers, carrying out tasks in accordance with school programs so that goals can be achieved properly through optimal performance.